Potentials of Serbia for business tourism development - Podovac Milena; Milićević Snežana (Ekonomski Pogledi, 2013)
Business tourism is one of the fastest growing segments of the tourism industry. Globalization, economic trends, development of science and information technology and business expansion in the international market created the need for exchange of knowledge, information and experience. Continuous growth of the world economy and global events predicted the intensive cooperation of experts from around the world, including the growth of business tourism. The subject of this work is an analysis of business tourism of Serbia and potentials for developing competitive destinations in this tourism segment. At the very begining we define concept of business tourism, basic characteristics and classification. In order to highlight the importance of business tourism, we present international tourism market results through years 2010 and 2011. This work analyzes also the potentials of Serbia for development of business tourism and representative destination. To develop guidelines for improving the current position on business travel market we use modern trends from business tourism as well as the actual situation of Serbia and its main destinations. Based on analysis of the overall potential for business tourism development, a choice of adequate marketing mix combination and engagement of tourism offer carrier can be a crucial factor in determining business tourism products.